2020
DOI: 10.1186/s12955-020-01462-5
|View full text |Cite
|
Sign up to set email alerts
|

The development and cognitive testing of the positive outcomes HIV PROM: a brief novel patient-reported outcome measure for adults living with HIV

Abstract: Background: People living with HIV experience burdensome multidimensional symptoms and concerns requiring person-centred care. Routine use of patient reported outcome measures can improve outcomes. There is no brief patient reported outcome measure (PROM) that currently reflects the breadth of concerns for people living with HIV. This study aimed to develop and cognitively test a brief novel patient reported outcome measure for use within routine adult HIV care-the "Positive Outcomes" HIV PROM. Methods: Develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…The selected issues are quite similar to those chosen for inclusion in a recent PROM developed by Bristowe et al (2020) and colleagues on the basis of research conducted in England and Ireland. Those authors have reported the content and face validity of their new instrument.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected issues are quite similar to those chosen for inclusion in a recent PROM developed by Bristowe et al (2020) and colleagues on the basis of research conducted in England and Ireland. Those authors have reported the content and face validity of their new instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the contribution that this type of PROM could make to routine clinical care, this remains an area under development. The only such instrument that we are aware of in the HIV field is currently being developed by Bristowe et al (2019Bristowe et al ( , 2020, with the content of the instrument guided by qualitative research involving PLHIV and other key stakeholders in England and Ireland.…”
Section: Introductionmentioning
confidence: 99%
“…Another concern with PROMs is that they are likely to be more precise in capturing patient perceptions and their variation over time in homogeneous target populations, such as patients within a set range of disease severity [94]. This may limit their generalisability to large, multicentre and multinational clinical trials with widespread geographic, cultural and socioeconomic differences between participating patient populations [95]. Furthermore, if a wide range of disease severity is represented in a therapeutic trial, the realistic patient goals, expectations and perceptions may further vary greatly.…”
Section: Challenges Of Proms: Development Validation and Implementation Problems In Developmentmentioning
confidence: 99%
“…Several questionnaires can assess the patient’s QoL in a general way, including the Pittsburgh Sleep Quality Index, the EuroQol-5D (EQ-5D), the 12-Item Short Form Health Survey (SF-12), the 20-Item Short Form Health Survey (SF-20) and the 36-Item Short Form Health Survey (SF-36). More specifically, the King’s College ‘Positive Outcomes’, 125 the HIV Symptom Index (HIV-SI), the WHO Quality of Life in HIV-infected Persons instrument (WHOQOL-HIV), the HIV-QOL and the Patient Reported Outcomes Quality of Life-HIV (PROQOL-HIV) 126 are used for HIV patients.…”
Section: Qolmentioning
confidence: 99%
“…124 , 127–130 PROs are emerging as one of the key areas for exploring HIV infection as a chronic disease with an almost normal life expectancy. 125 , 131–134 The maintenance of both long-term physical and mental health is considered the main challenge for HIV medicine, but these variables can be missed by health professionals in busy appointments. Thus, the routine use of PROs may help to identify patients’ problems and concerns and improve their progress by revealing and managing these issues.…”
Section: Qolmentioning
confidence: 99%